Handling of Sticky Coal During the Process of Unloading Coal from the Wagon at Kertapati Port - Afin, Bayu Pramana; Utama, Akbar Adhi (Universitas Pamulang, 2025)
Coal unloading operations at Kertapati Port face persistent inefficiencies due to the adhesive nature of low-rank coal, which frequently sticks to the inner surfaces of train carriages, causing delays, increased operational costs, and reduced unloading performance. This study aims to formulate a feasible and effective strategy to mitigate the issue of sticky coal during the unloading process to support the achievement of production and transportation targets. Using a mixed-methods approach, the study integrates the Current Reality Tree (CRT) to identify root operational bottlenecks, the Analytic Hierarchy Process (AHP) to prioritize technical solutions, the Critical Path Method (CPM) and PERT for project scheduling, and financial feasibility analysis through NPV, IRR, and Payback Period. The results indicate that applying a stainles steel lining to the interior of boat-type train carriages is the most effective solution to reduce coal adhesion. Financially, the proposed investment is attractive, yielding an IRR of 66%, an NPV of IDR 29.1 billion, and a payback period of two years. The project is scheduled to begin on August 1, 2025, and complete by November 14, 2025. Continuous risk management measures are also planned throughout implementation. This integrated solution not only addresses the immediate operational inefficiencies but also supports long-term improvements in coal handling reliability and port logistics performance.